Higher Education in Hospitality, Tourism and Leisure in Portugal - Brites Salgado, Manuel António (2021)
The analysis of higher education in the area of ​​Hospitality, Tourism and Leisure aims to understand the evolution of the offer and demand of this area of ​​knowledge in Portugal, which necessarily requires a contextualization of educational policies at National and European level. In a first phase, it is observed that the Bologna Process led to changes in the structure and organization of the courses, namely at the curriculum level and the teaching-learning process. In a second phase, there is a reorganization of the existing training offer and a large number of new study cycles proposed to A3ES for accreditation. According to the Portuguese National offer in this area, we analyze a case study (ESTH-IPG), which is based on Tourism and Hospitality. It pretends to know the process of evolution of the courses of this School, according to the models of curricular organization in each phase, mainly through the collection and analysis of secondary information on the main indicators, in order to understand differences between three formative aspects: Tourism, Hospitality and Catering. The strategy to be adopted by the School, at regional and national level, must be based on structured knowledge of the internal context to better position itself in the external environment.